Comparison of aggressiveness among groups of sportsmen according to selected types of sports - Greganova, M. (European Researcher. Series A, 2018)
The aim of the research was to find out the different types of aggressiveness among sportsmen performing individual sports and then compare the results obtained among selected types of sports. The theoretical analysis of the aggressiveness issue was carried out on the basis of a literature study, which is also based on an empirical research. A standardized psychological questionnaire B - D - I, aimed at diagnosing aggression, was used to obtain the factual material. We analyse and compare the values obtained on the basis of the psychological questionnaire B - D - I and interpret the results obtained. For better clarity, we provide measured values in the form of tables and figures. In the subtest irritability the highest initial measurements (IM) were reached in the value 9,1 which indicates significant rise of the level of the given type of aggressiveness. One respondent belonging to the file B (cross-country skiing) and one respondent from the file D (fitness and body building) have this high extent of irritability. By testing the level of negativism and subsequent comparison of the median values between individual sets, we have achieved results that point to the dominant occurrence of this type of aggressiveness in the file C (cycling). The analysis of the results related to the occurrence of the level of resentment in the individual examined files showed the highest IM rate of 8.75. Such IM values were measured in two sets, namely in the group B (cross-country skiing) and D (fitness and bodybuilding).